Complete Genome Sequences of Curli-Negative and Curli-Positive Isolates of Foodborne Escherichia coli O157:H7 Strain 86-24 - Sharma, Vijay K. (Genome Announc, 2016)
Escherichia coli O157:H7 strain 86-24 does not produce curli fimbriae, but gives rise to curli-positive isolates at a variable frequency. Here, we report the complete genome sequences of curli-negative and curli-positive isolates of strain 86-24.